O europeu e o outro (The European and the other) - Santos, Rafael Chaves (Estudos da Língua(gem), 2013)
A primeira grande Expedição Científica Austríaca ao Brasil no início século XIX produziu, além da coleta de diversas espécies e peças de coleções antropológicas e etnográficas, vários relatos das experiências de seus participantes. Um destes, Johann Natterer, cuja permanência em nossas terras foi a mais demorada, não pode em vida concluir sua obra, mas deixou centenas de cartas que relatam suas experiências e vivências pelas regiões do Brasil. Seus textos, ainda pouco trabalhados no Brasil, são, neste artigo, analisados como prática social que busca evidenciar por meio da linguagem posições ideológicas de caráter eurocêntrico. PALAVRAS-CHAVE: Europeus. Relatos. Linguagem. Índios. ABSTRACT The first major Austrian Scientific Expedition to Brazil in early nineteenth century produced, in addition to collecting various species and parts of anthropological and ethnographic collections, many compilations of the experiences of their participants. One of these, Johann Natterer, whose permanence in our land was the most time consuming, could not complete his work in life time, but left hundreds of letters that described his knowledge and his experiences of life in the regions of Brazil. This article analyses his texts, which had not been yet studied in Brazil, as a social practice that seeks to demonstrate through language the Eurocentric ideological character. KEYWORDS: Europeans. Reports. Language. Indians.